Kualitas Jasa, Harga dan Pengaruhnya Terhadap Kepuasan Pelanggan - Edwar M Nur; Chairul Ichsan (Center for Research and Community Service (LPPM) University of Abulyatama, 2018)
This business emerged in response to the demands of people who wanted an efficient form of time-care business. The need for auto repair shops and car salon in one roof has increased. Therefore the market potential of this field of business is very large. The purpose of this study is to determine the effect of service quality and price simultaneously on customer satisfaction of Sehat Workshop in Banda Aceh, to know the effect of service quality partially on customer satisfaction of Sehat Workshop in Banda Aceh and to know the effect of price partially on customer satisfaction Sehat Workshop in Banda Aceh . This research was conducted at Sehat workshop branch of Banda Aceh which is located at P.Nyak Makam Street. No.167. Lambhuk Kota Banda Aceh, while the object of this study is about the quality of service and customer satisfaction using the service of Sehat Workshop Banda Aceh, with the number of respondents as many as 150 people. The results showed that the quality of services and prices together significantly affect the satisfaction of consumers Sehat Workshop in Banda Aceh, then the quality of service products from the Sehat Workshop individually significantly affect the satisfaction of consumers of service users Sehat Workshop Banda Aceh and individually prices given by Sehat Workshop individually have an effect on significantly to customer satisfaction of service user of Sehat Workshop of Banda Aceh.